2020
DOI: 10.21203/rs.3.rs-97694/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Survival and Predictors of Mortality Among Patients Admitted to Intensive Care Unit in Southern Ethiopia: A Multi-center Retrospective Cohort Study

Abstract: Background: The burden of life-threatening conditions requiring intensive care unit has grown substantially in low-income countries related to an emerging pandemic, urbanization, and hospital expansion. The rate of ICU mortality is varied from region to region in Ethiopia. However, body of evidence on ICU mortality and its predictors is uncertain. This study was designed to investigate the pattern of disease and predictors of mortality in Southern Ethiopia.Methods: After obtaining Ethical clearance from instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
(62 reference statements)
1
2
0
Order By: Relevance
“…Mechanically ventilated patients have a very high mortality rate in our ICU, which is comparable with data from other low- and middle-income countries [ 9 , 13 , 18 ]. A low Glasgow Coma Scale, a cardiovascular diagnosis, and a very low serum albumin level were independent predictors of death in multivariable logistic regression.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Mechanically ventilated patients have a very high mortality rate in our ICU, which is comparable with data from other low- and middle-income countries [ 9 , 13 , 18 ]. A low Glasgow Coma Scale, a cardiovascular diagnosis, and a very low serum albumin level were independent predictors of death in multivariable logistic regression.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, there are no respiratory therapists in the medical and surgical ICUs. Mechanical ventilators are managed by clinicians with limited training [ 18 ], potentially affecting patient outcomes. Second, similar to other studies [ 5 , 13 , 18 ], we found that patients with low GCS were more likely to die.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation